The Relationship of Self-Control with Bullying Behavior in Class 7 Junior High School Students: Hubungan Kontrol Diri dengan Perilaku Bulying Pada Siswa Kelas 7 Sekolah Menengah Pertama - Affandi, Ghozali Rusyid; Putra, Buyung Ariza (Universitas Muhammadiyah Sidoarjo, 2022)
The existence of bullying behavior carried out by students to their friends is a matter of concern because bullying has a very bad impact on the psychic who is exposed to bullying. Bullying should be avoided by strengthening self-control in students. The purpose of this study was to determine the relationship between self-control and bullying behavior in class VII SMPN X. This research will be conducted using a correlational quantitative approach. This study used a sample of 186 students who were obtained from random sampling techniques. The data collection technique was done using a psychological scale. Measurement of variables using a Likert scale. The bullying behavior scale reliability was 0.747 and the self-control scale was 0.881. The data analysis technique is done by testing the hypothesis using Pearson Correlation Product Moment. The results of this study indicate that there is a relationship between self-control and bullying behavior in SMP X students in Sidoarjo. The relationship between self-control and bullying behavior is 0.819 with a sig value. 0,000. Increased student self-control will have an impact on reducing bullying behavior, as well as a decrease in student self-control will result in an increase in bullying behavior. The amount of influence between self-control and bullying behavior is 0.671 or 67.1%. The students' self control at SMP X in Sidoarjo was classified as moderate, while the bullying behavior at SMP X in Sidoarjo was low.